Enhancing Narrative Writing Skills Through Experiential Learning In Pre-Service Teacher Practicum: A Classroom-Based Study In The PPG Program - Baharuddin Baharuddin; Arjudin Arjudin; Syaiful Musaddat; Arafiq Arafiq; Herlyana Hasyim (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2025)
The Teacher Professional Education Program (PPG) in Indonesia still has problems in developing narrative writing skills in the practicum stage. This classroom action research is therefore aimed at discovering the effect of systematic application of Kolb’s Experiential Learning Cycle system (CE, RO, AC, and AE) in the practicum experience in PPG on the improvement of narrative writing skills of high school students. In this article, we collected data from 36 students of Grade XI of SMAN 2 Mataram and a pre-service teacher of PPG through a narrative writing task, observation, and a reflective journal. In total, six dimensions were analysed: narrative structure, outline development, cohesion, vocabulary, word count accuracy and writing mechanics. Results showed definite improvements with average scores going from 83 to 89, and general improvement in consistency throughout the class. The greatest improvements were in coherence, writing mechanics, and outline development. The findings indicate that Kolb’s cycle enhances students’ writing outcomes as well as the professional development of pre-service teachers in practice at their teacher schools by incorporating writing cycle activities and applications into their teaching.